ANALYSIS OF MECHANICAL PROPERTIES OF RECYCLED ALUMINUM PISTON CASTINGS - Hanafi, Mohammad; Hadi, Syamsul (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
The use of aluminum is increasing in the industrial sector, which is accompanied by an increase in aluminum waste if it is not handled quickly and appropriately, which will have a negative impact on the environment. Recycling is an alternative to overcome this problem. Recycling piston waste into pistons, data was obtained that there are insoluble aluminum elements, namely Cu, Fe, Si. The aim of this research is to determine the effect of recycling aluminum into pistons by tensile and impact testing with the addition of Cu 0.5%-1.5% & Fe 1%-1.5% with various tensile test speeds of 5mm/minute, 10mm/minute, and 15mm/min. The research uses independent variables, namely the addition of Cu & Fe to aluminum waste and the dependent variable is tensile strength testing and specific impact strength. The results of this research can determine how much Fe and Cu content is added in order to reach the standard piston content, increasing the hardness of aluminum without reducing the hardness and ductility too much, which is known from the strength values of recycled aluminum pistons through specific tensile and impact tests with average stress values. The highest was in Cu 1% - 1.5% & Fe 1% - 1.5% alloy with a tensile testing speed of 11 mm/minute of 196.19 MP, while the lowest stress value was obtained from Copper (Cu) 1% - 1.5 % & Iron (Fe) 0.5%-1% with a tensile testing speed of 8 mm/minute of 120.72 N/m2. The largest impact energy for aluminum piston specimens was obtained at 0.294 J in 1% - 1.5% Copper (Cu) and 1% - 1.5% Iron (Fe) alloys.